2022
DOI: 10.1021/acs.jpcc.2c02431
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Topological Transition of 2D Boron by the Ion Exchange Reaction

Abstract: We systematically investigated electronic evolutions of nonsymmorphic borophene with chemical environments that were realized by the ion exchange method. Electronic structures can be characterized by the topological invariant. Spectroscopic experiments and DFT calculations unveiled that a sheet of hydrogenated borophene (borophane) is the Dirac nodal loop semimetal ( ), while a layered crystal of YCrB4 is an insulator ( ). The results demonstrate the electronic topological transition by replacement of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Furthermore, theoretical studies have revealed their intriguing electronic [ 9 ], optical, and thermal properties [ 10 , 11 ], as well as their possible applications in hydrogen release devices [ 12 , 13 ], reversible hydrogen storage [ 14 ], current limiters [ 15 ], photodetectors, individual amino acid sensors [ 16 ], rechargeable Li/Na ion battery electrodes [ 17 , 18 ], and anodes for rechargeable potassium-ion batteries, with high capacities, low voltages, and high rate performance [ 19 ]. Furthermore, the formation of HB sheets has paved the way for the conceptual development of new types of HB materials [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, theoretical studies have revealed their intriguing electronic [ 9 ], optical, and thermal properties [ 10 , 11 ], as well as their possible applications in hydrogen release devices [ 12 , 13 ], reversible hydrogen storage [ 14 ], current limiters [ 15 ], photodetectors, individual amino acid sensors [ 16 ], rechargeable Li/Na ion battery electrodes [ 17 , 18 ], and anodes for rechargeable potassium-ion batteries, with high capacities, low voltages, and high rate performance [ 19 ]. Furthermore, the formation of HB sheets has paved the way for the conceptual development of new types of HB materials [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecule 2:4:6:8:-2H-1,5:1,5-ÎŒH-B 8 H 10 has a five-membered boron ring on each of the two sides of the 3c-2e bond, as shown in Figure 1 b,c. The topological borophane layer (α-HB sheet) reported recently also has such a pair of five-membered rings in its sheet structure, as shown in Figure 4 a,b [ 12 , 13 ]. Among the different arrangements, the pair unit is the tiled ÎČ-HB sheet ( Figure 4 c,d).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that its kinetic stability was supported by the positive vibrational energy of the phonon modes. This material was successfully synthesized through an ion-exchange reaction [ 12 , 13 ]. The α-HB sheet is a semimetal, with electronic states of the Dirac nodal loop (DNL) at the Fermi level.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations